2020
DOI: 10.1038/s41598-020-71349-4
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric sensing of imidacloprid in cucumber fruits using a graphene quantum dot/Au (III) chemosensor

Abstract: the current research presents a very simple method for the colorimetric detection of imidacloprid using a graphene quantum dot/Au (iii) chemosensor. the results demonstrated that there is an interaction between Au 3+ ions and the imidazole group of the pesticide toward reduction of Au 3+ to Au 0 in the presence of graphene quantum dots. this phenomenon changes the color of gold nanoparticles from yellow to grey or red, and causes a shift in the peak of localized surface plasmon resonance (LSpR) as gold nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…It must be mentioned that the obtained LOD value of 0.75 ppb is extremely competitive considering the imidacloprid detection systems reported in the literature. [13][14][15][16][17][18] Moreover, we believe that our work represents an outstanding result considering that is the first example of imidacloprid detection achieved using a LSPR tool.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It must be mentioned that the obtained LOD value of 0.75 ppb is extremely competitive considering the imidacloprid detection systems reported in the literature. [13][14][15][16][17][18] Moreover, we believe that our work represents an outstanding result considering that is the first example of imidacloprid detection achieved using a LSPR tool.…”
Section: Resultsmentioning
confidence: 74%
“…17 Among the variety of transduction elements that can be adopted for the simple, label-free, cost-effective and on-site investigation of hazardous agents to ensure environmental protection and food safety, localized surface plasmon resonance (LSPR) has proved to be particularly favourable. 18 This phenomenon exploits a coherent oscillation of the conduction electrons generated in metallic nanoelements upon interaction with photons of appropriate wavelength, causing both transmitted light attenuation and electric near-field amplification. Refractive index (RI) variations due to the deposition of molecules on the metallic surface can be simply and promptly revealed by evaluating the red shift of the wavelength associated with the transmitted light minimum, allowing a quantitative label-free analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The regressions at different PANI concentrations show p -values which are smaller than 0.01; thus, these regressions are significant. Besides, all the starch/PANI films show good linearity in ammonia sensing with coefficient correlation (R 2 ) > 0.90 [ 71 ]. The starch/PANI 0.1% to 0.4% films also show precise sensing performance with acceptable reproducibility as they have a relative standard deviation (RSD) which is lower than 10% (n = 3) [ 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that the perching of Alizarine Red S on GQD generates a powerful sensor for detecting metal cations 23 . Easy, rapid, and cost-effective synthesis of GQD in combination with sustainability, and facile modification are some characteristics of this material that encouraged us to its modification with EBT 24 26 . Therefore, GQD was modified with EBT (GQD-EBT) to obtain a novel sensor of metal cations via esterification reaction (Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%